Novel Functional APOB Mutations outside LDL-Binding Region Causing Familial - Alves, A.C. (2013)
Funded by FCT SFRH / BD / 27990 / 2006 and FCT_PTDC/SAU-GMG/101874/2008; project grant FCT_PTDC/SAU-GMG/101874/2008.